Physical growth measurements of preschool urban Turkish children - Yalaz, Kalbiye; Epir, Shirley (The Turkish Journal of Pediatrics, 1983)
Height, weight, head and chest measurements were obtained for 1089 children aged between 15 days and 6 years 4 months. The sample included only healthy children and represented the various socio-economic levels in the city of Ankara. Growth charts and graphs were prepared separately for boys and girls. Recommendations for their use were considered.
Keywords: physical measurements; Turkish urban children; height; weight; head measurement